2021
DOI: 10.24926/iip.v12i4.4208
|View full text |Cite
|
Sign up to set email alerts
|

Why Nigeria Must Strengthen its Local Pharmaceutical Manufacturing Capacity

Abstract: With over 115 registered pharmaceutical manufacturers, Nigeria still depends on other countries for the supply of active pharmaceutical ingredients and excipients. Significant attention has not been paid to the local production of raw materials, pharmaceutical dosage formulations, or processing equipment, which has resulted in a decline in the country's pharmaceutical manufacturing capacity. Owing to the overall importance of the pharmaceutical industry, it is, therefore, essential to pay close attention to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…As a matter of fact, Africa's local pharmaceutical manufacturing is greatly reliant on imported commodities and industrial machinery, and this dependency is a major challenge for Africa's health resilience [ 56 ]. For example, In Nigeria, significant attention has not been paid to the local production of raw materials, and due to the lack of domestic production of key inputs such as Active Pharmaceutical Ingredients (APIs), the country is forced to rely on foreign countries like India and China for supply, which causes a hike in prices and foreign exchange difficulties [ 58 ]. Furthermore, among the 54 countries in Africa, there are just 8 countries that have industries operating across the vaccine-manufacturing landscape, of which only 1 (Senegal) has the pre-qualification from the WHO to export vaccines [ 59 ].…”
Section: The Need To Prioritize Vaccine Development and Research In A...mentioning
confidence: 99%
“…As a matter of fact, Africa's local pharmaceutical manufacturing is greatly reliant on imported commodities and industrial machinery, and this dependency is a major challenge for Africa's health resilience [ 56 ]. For example, In Nigeria, significant attention has not been paid to the local production of raw materials, and due to the lack of domestic production of key inputs such as Active Pharmaceutical Ingredients (APIs), the country is forced to rely on foreign countries like India and China for supply, which causes a hike in prices and foreign exchange difficulties [ 58 ]. Furthermore, among the 54 countries in Africa, there are just 8 countries that have industries operating across the vaccine-manufacturing landscape, of which only 1 (Senegal) has the pre-qualification from the WHO to export vaccines [ 59 ].…”
Section: The Need To Prioritize Vaccine Development and Research In A...mentioning
confidence: 99%
“…Other challenges that LPMs encounter in the DRC include unsatisfactory and costly utilities, rising transportation expenditures, and corruption. Other African countries, particularly Nigeria, have reported similar incidents [12]. Consumers, on the other hand, believe that locally manufactured pharmaceutical products are of inferior quality, thus pharmacies are unwilling to stock them [8].…”
Section: State Of Local Pharmaceutical Manufacturing In the Drcmentioning
confidence: 99%
“…Also, it was revealed that pharmaceutical manufacturing companies in Zimbabwe could not produce pharmaceutical starting materials such as APIs. In Africa, very few countries such as South Africa [ 9 ], Ghana [ 9 ], and Nigeria [ 10 ] have witnessed relative success in plans to start the local manufacture of APIs. All the pharmaceutical companies in Zimbabwe are solely limited to the manufacture of pharmaceutical products from already-imported APIs, and the repackaging of already finished pharmaceutical dosage forms into capsules, tablets, or other packaging materials.…”
Section: The Zimbabwean Pharmaceutical Industry: Challenges and Insig...mentioning
confidence: 99%
“…The disparity in access to COVID-19 vaccines between high- and low- and middle-income countries (LMICs) is still widening as LMICs such as Zimbabwe are struggling with a severe lack of COVID-19 vaccines [ 14 ]. Given that LMICs lack the capacity to produce COVID-19 vaccines [ 10 , 11 , 15 ], a call for big pharmaceutical companies to temporarily abolish the intellectual property (IP) rights on their COVID-19 vaccines was proposed by India and South Africa in October 2020 but this was met with significant opposition and resistance [ 16 , 17 , 18 ]. This waiver was intended to allow LMICs to manufacture COVID-19 vaccines -via technical and technology transfer- without compensating the big pharmaceutical companies.…”
Section: Can Zimbabwe Produce Covid-19 Vaccines?mentioning
confidence: 99%